Chromium‐induced diffuse dermatitis with lymph node involvement resulting from Langerhans cell histiocytosis after metal‐on‐metal hip resurfacing. (15th March 2015) - Bizzotto, N.; Sandri, A.; Trivellin, G.; Magnan, B.; Micheloni, G.M.; Zamò, A.; Bernardi, P.; Sbarbati, A.; Regis, D.
Summary: Total hip arthroplasty (THA) is a highly effective surgical treatment for severe joint involvement. However, due to the release of metal ions in the blood, the patients who undergo hip replacement with metal‐on‐metal (MOM) bearings may develop signs of allergic skin disease. We report a case of a 60‐year‐old man who had received MOM hip resurfacing 5 years earlier for osteoarthritis. He presented with a 3‐year history of diffuse dermatitis that did not respond to antihistamines and corticosteroids and also had elevated serum levels of chromium and cobalt. A patch test revealed chromium‐sulfate hypersensitivity. A skin biopsy showed nonspecific perivascular lymphocytic infiltrate associated with histiocytes. A biopsy of an inguinal lymph node demonstrated large aggregates of Langerhans cells, suggesting type IV delayed‐type hypersensitivity. The prosthesis was replaced using ceramic‐on‐ceramic bearings and the dermatitis resolved after 3 months. The lymph nodes decreased in volume and the serum chromium levels normalized within 24 months of revision surgery. The high levels of serum ions associated with the metal debris from MOM‐THAs may induce sensitization and type IV hypersensitivity reactions. Replacing the prosthesis using alternative coupling surfaces is the only approach that has the capacity to resolve these symptoms. Physicians who are not familiar with this issue may misdiagnose systemic symptoms and provide inadequate treatment. Abstract : What's already known about this topic? Metal‐on‐metal (MOM) hip resurfacing (HR) is frequently associated with metallic corrosion, the release of wear debris and high levels of metal ions in the blood. Systemic and local signs of prolonged exposure to metal ions include hypersensitivity, possible carcinogenicity and pseudotumour formation. Metal‐related dermatitis and lymphadenopathy after orthopaedic joint prostheses are well known. What does this study add? Combined diffuse dermatitis with lymph node involvement resulting from Langerhans cell histiocytosis induced by chromium after MOM‐HR has not been previously reported. Prolonged release of metal ions and high serum levels may cause sensitization and type IV hypersensitivity reaction to chromium. Lymphadenopathy with diagnosis of special Langerhans cell histiocytosis may be due to prolonged activation of the type IV immune response. Replacing the prosthesis using alternative coupling surfaces is the only approach that can resolve these symptoms.